Non-Gaussian tail in the force distribution: a hallmark of correlated disorder in the host media of elastic objects - Sanchez, J.A. (2020)
Fil: Sanchez, J.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina